Antigastric autoantibodies in Helicobacter pyloriinfection: implications of histological and clinical parameters of gastritis. Issue 5 (1st November 1997) - Faller, G; Steininger, H; Kränzlein, J; Maul, H; Kerkau, T; Hensen, J; Hahn, E G; Kirchner, T
Abstract : Background —It has recently been shown that humoral antigastric autoreactivities occur in a substantial number of Helicobacter pylori infected patients. Aims— To analyse the relevance of such antigastric autoantibodies for histological and serological parameters of the infection as well as for the clinical course. Methods —Gastric biopsy samples and sera from 126 patients with upper abdominal complaints were investigated for evidence of H pylori infection using histology and serology. Autoantibodies against epitopes in human gastric mucosa were detected by immunohistochemical techniques. Histological and clinical findings of all patients were then correlated with the detection of antigastric autoantibodies. Results — H pylori infection was significantly associated with antigastric autoantibodies reactive with the luminal membrane of the foveolar epithelium and with canalicular structures within parietal cells. The presence of the latter autoantibodies was significantly correlated with the severity of body gastritis, gastric mucosa atrophy, elevated fasting gastrin concentrations, and a decreased ratio of serum pepsinogen I:II. Furthermore the presence of anticanalicular autoantibodies was associated with a greater than twofold reduced prevalence for duodenal ulcer. Conclusion —The data indicate that antigastric autoantibodies play a role in the pathogenesis and outcome of H pylori gastritis, in particular in the development of gastric mucosal atrophy.